Features of development of Russian economy in conditions of transformation of competitive environment - V. I. Sribnuj (Омский научный вестник: Серия "Общество. История. Современность")
In this article, the author proposes priority trends that determine the features of socio-economic development considered in the context of the influence of four factor groups (social, political, economic, and technological groups of factors). The main problems at the present stage of development of the Russian economy are considered as a whole and individual economic entities are highlighted. The state of the Russian economy and specifics of development of the Russian economy in the conditions of transformation of competitive environment are observed. The author defines the reasons that negatively affect the development of the national socio-economic system